Contraceptive pills induce an improvement in congenital hypoplasminogenemia in two unrelated patients with ligneous conjunctivitis - Sartori, Maria Teresa; Saggiorato, Graziella; Pellati, Donatella; Casonato, Alessandra; Spiezia, Luca; Pontara, Elena; Gavasso, Sabrina; Girolami, Antonio (Thrombosis and Haemostasis, 2003)
Severe type I plasminogen deficiency is the underlying cause of ligneous conjunctivitis, a rare disease characterized by wood-like pseudomembranes developing on the ocular and extraocular mucosa. Two unrelated female patients with ligneous conjunctivitis and moderate hypoplasminogenemia are described. Being of fertile age, they were treated with oral contraceptives, which determined a marked increase in plasminogen levels. Moreover, a palpebral pseudomembrane stopped growing in one patient and disappeared completely in the other while on the estroprogestinic treatment. In patient n.2,who also suffered from von Willebrand’s disease, prior Cushing’s disease induced an increase in both von Willebrand factor and plasminogen levels, which dropped after curative hypophysectomy. Genetic plasminogen study showed a 19Lys>Glu mutation in a heterozygous state in the first proposita and in a homozygous state in the second proband. In addition, both index patients were homozygous for a new intron F-14T>G mutation, which was found to reduce the acceptor splicing site prediction score.In conclusion, oral contraceptive therapy may improve plasminogen deficiency and deserves attention as an alternative therapeutic approach in selected cases of ligneous conjunctivitis with low, but not absent, plasminogen synthesis.
Keywords: Plasminogen deficiency; ligneous conjunctivitis; oral contraceptives; plasminogen gene mutations; von Willebrand’s disease